PROFITABILITY AND THE FIRM'S VALUE - Jonnius, Jonnius; Setya Marsudi, Almatius (Dinasti Publisher, 2021)
The cause of this research is to investigate and prove the impact of ROA, ROE, NPM, and GPM on firm’s value (Tobin's Q) either partially or simultaneously and decide which profitability ratio is more dominant in explaining Tobin's Q variance. The analysis was carried out on companies listed in the Jakarta Islamic Index (JII) for 2015-2020. The sample selected was issuers consistently registered with JII during the 2015-2020 period, and 11 issuers were selected. The results of the analysis show ROA and NPM partially sizeable good-sized effect on Tobin's Q, whilst ROE and GPM do not have any effect. ROA is positively correlated, and NPM is negatively correlated. However, all independent variables simultaneously have a significant impact on Tobin's Q. The R-square value of is 0.953648 shows that 95.37% of Tobin's Q variance can be explained by changes in ROA, ROE, GPM, and NPM, while other factors outside the model cause the remaining 4.43%. Of the four variables tested, ROA is the more dominant variable affecting Tobin's Q and can be used as the best proxy for corporate profitability.